Application of 2D Seismic Modeling in Gas Hydrate Reservoir Characterization - Welayaturromadhona, Welayaturromadhona; Chen, How Wei (Departemen Geofisika, FMIPA - Universitas Hasanuddin, Makassar, 2025)
Gas hydrate reservoirs represent a significant unconventional energy resource with considerable potential for future energy supply and climate-related studies. However, their complex subsurface occurrence requires advanced geophysical methods for accurate detection and characterization. This study presents the application of two-dimensional (2D) seismic modeling to evaluate the seismic response of gas hydrate-bearing sediments and underlying free gas zones. The objective is to assess the reflection coefficients and amplitude variation with offset (AVO) to enhance the interpretation of subsurface features. The synthetic model is constructed using multichannel seismic data and velocity profiles derived from previous studies. Seismic wave propagation is simulated to observe the impedance contrasts across various subsurface layers. Results reveal that the Bottom Simulating Reflector (BSR), a key seismic indicator of gas hydrate presence, exhibits strong negative reflection amplitudes due to the presence of underlying free gas, which significantly reduces seismic velocity. Furthermore, AVO analysis shows that amplitude variations are highly sensitive to the acoustic impedance contrast at the hydrate-gas interface. These findings demonstrate the effectiveness of seismic modeling in improving gas hydrate reservoir characterization and provide a foundation for more accurate exploration strategies. The study contributes to both energy development and environmental monitoring efforts involving gas hydrates.